Kwashiorkor dengan Crazy Pavement Dermatosis - Mauliza; Venanda, Natasya (Lembaga Pengembangan Kinerja Dosen, 2025)
Kwashiorkor is a form of protein energy malnutrition (MEP). Malnourished toddlers have short and long term effects, in the form of impaired growth and development, including impaired cognitive function, morbidity, risk of degenerative diseases in later life and death. The male patient aged 1 year and 2 months was brought by his parents to the emergency room of Cut Meutia Hospital on Tuesday, June 4, 2024 at 20:07 WIB with complaints of swelling on both backs of legs and hands and face. On the antopometric examination on the first day of treatment, the patient's nutritional status was found to be poor. Patients are given malnutrition management which is divided into 3 phases, namely stabilization, transition and rehabilitation. Kata kunci: Antropometri, Kwashiorkor, Malnutrisi Energi Protein